tEACHING AND LEARNING: AN EXPERIENCE WITH GROUPS OF PARENTS OF HOSPITALIZED CHILDREN - Denize Bouttelet Munari; Ruth Minamisava; Ida Kuroki Borges; Lizete Malagoni de A. C. Oliveira; Lourdes Maria Silva Andraus (Universidade Federal de Goias, 2004)
This paper intends to retell an experience in the practical teaching of Enfermagem Materno-Infanto-Juvenil, involving nursing care for guardians of hospitalized children through team work coordinated by nursingstudents. The aim was to describe the experience in using group technology as a strategy in order to assisthospitalized childrens guardians and also to show nursing students the importance of helping this group of clients.The team work with these guardians has been very efficient to show their real needs. In addiction to that it allowsthe socialization of the subject experiences related to the childs hospitalization and the search for healthierbehaviors to face the situation. This technology was also effective to provide students the opportunity to deal withtheoretical aspects of the nurse-patient-family relation, raising their interest in helping those in charge of making thechildren company. In conclusion, the usage of team techniques for the assistance of hospitalized children providesthe development of sensitivity and personal growth of students and parents, besides improving the quality of theoffered nursing care.